The Immune System in Transfusion-Related Acute Lung Injury Prevention and Therapy: Update and Perspective - Guo, Kai; Ma, Shuxuan (Frontiers in Molecular Biosciences, 2021)
As an initiator of respiratory distress, transfusion-related acute lung injury (TRALI) is regarded as one of the rare complications associated with transfusion medicine. However, to date, the pathogenesis of TRALI is still unclear, and specific therapies are unavailable. Understanding the mechanisms of TRALI may promote the design of preventive and therapeutic strategies. The immune system plays vital roles in reproduction, development and homeostasis. Sterile tissue damage, such as physical trauma, ischemia, or reperfusion injury, induces an inflammatory reaction that results in wound healing and regenerative mechanisms. In other words, in addition to protecting against pathogens, the immune response may be strongly associated with TRALI prevention and treatment through a variety of immunomodulatory strategies to inhibit excessive immune system activation. Immunotherapy based on immune cells or immunological targets may eradicate complications. For example, IL-10 therapy is a promising therapeutic strategy to explore further. This review will focus on ultramodern advances in our understanding of the potential role of the immune system in TRALI prevention and treatment.